2003
DOI: 10.1093/emboj/cdg548
|View full text |Cite
|
Sign up to set email alerts
|

scribble mutants cooperate with oncogenic Ras or Notch to cause neoplastic overgrowth in Drosophila

Abstract: Cancer is a multistep process involving cooperation between oncogenic or tumor suppressor mutations and interactions between the tumor and surrounding normal tissue. Here we present the first description of cooperative tumorigenesis in Drosophila, by using a system that mimics the development of tumors in mammals. We have used the MARCM system to generate mutant clones of the apical–basal cell polarity tumor suppressor gene, scribble, in the context of normal tissue. We show that scribble mutant clones in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

44
833
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 572 publications
(879 citation statements)
references
References 48 publications
44
833
2
Order By: Relevance
“…In this regard, the CagA-PAR1-SHP-2 complex has a dual function; disruption of the epithelial polarity and aberrant activation of the Ras-MAPK pathway, indicating that the protein complex coordinates cell polarity defects and oncogenic signaling to promote epithelial cell transformation (Saadat et al, 2007). Such functional cooperativity has already been indicated by the observation that tumors induced by an oncogenic Ras in Drosophila do not have metastatic potential, whereas those induced by oncogenic Ras under the condition of loss of heterozygosity for lgl, dlg and scrib show more malignant phenotypes and frequently metastasize (Brumby and Richardson, 2003;Pagliarini and Xu, 2003).…”
Section: Loss Of Epithelial Polarity In Cell Transformationmentioning
confidence: 98%
“…In this regard, the CagA-PAR1-SHP-2 complex has a dual function; disruption of the epithelial polarity and aberrant activation of the Ras-MAPK pathway, indicating that the protein complex coordinates cell polarity defects and oncogenic signaling to promote epithelial cell transformation (Saadat et al, 2007). Such functional cooperativity has already been indicated by the observation that tumors induced by an oncogenic Ras in Drosophila do not have metastatic potential, whereas those induced by oncogenic Ras under the condition of loss of heterozygosity for lgl, dlg and scrib show more malignant phenotypes and frequently metastasize (Brumby and Richardson, 2003;Pagliarini and Xu, 2003).…”
Section: Loss Of Epithelial Polarity In Cell Transformationmentioning
confidence: 98%
“…Recently, Drosophila tumor models have been established that are based on defined and reproducible genetic manipulation of tumor suppressor and oncogenes (Brumby and Richardson, 2003;Pagliarini and Xu, 2003). These models consist of cells that have defective cell polarity and activated Ras signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of polarity is induced by loss of Scribble (Scrib), which is required for apico-basal polarity together with Discs large (Dlg) and Lethal giant larvae (Lgl) (Stewart et al, 1972;. Ras signaling was augmented through overexpression of a constitutively active version of Ras, Ras V12 (Brumby and Richardson, 2003;Pagliarini and Xu, 2003). Cells that are mutant for scrib and simultaneously express Ras V12 proliferate in an uncontrolled manner, pile on top of each other (neoplastic growth) and gain the ability to migrate into surrounding tissues (Brumby and Richardson, 2003;Pagliarini and Xu, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, they found that disruption of cell polarity synergized with expression of Ras V12 , and gave rise to metastatic tumors that mimicked many characteristics of human cancers. Importantly, clonal loss of scrib and cell polarity alone resulted in poorly growing cells that were eventually eliminated from the tissue, and although Ras V12 expression caused modest hyperplasia, Ras V12 expression in scrib mutant cells not only reversed their growth defects, but synergized with loss of scrib producing highly proliferative cells that formed neoplastic cell masses able to migrate into adjacent tissues (Brumby and Richardson, 2003;Pagliarini and Xu, 2003). This emergent phenotype would not be predicted from the phenotypes of Ras V12 or scrib single mutant cells alone.…”
mentioning
confidence: 98%
“…The MARCM technique can produce clones of GFP-'marked' cells that are homozygous mutant in a gene and at the same time overexpress one or more other transgenes or dsRNAi of interest. The groups of Tian Xu and Helena Richardson used the MARCM system to elucidate the role of cooperation between multiple genetic events to promote neoplastic growth and metastasis in Drosophila (Figure 1; Brumby and Richardson, 2003;Pagliarini and Xu, 2003). In particular, they explored an interaction between disruption of apical-basal cell polarity, a defect that promotes the epithelial to mesenchymal transition often associated with cancer, by introducing a mutation in the neoplastic tumor suppressor gene scribble (scrib), which encodes a conserved scaffold protein that is essential for the maintenance of cell polarity (Humbert et al, 2008), and concurrent overexpression of a hyperactive version of the Ras oncogene (Ras V12 ), which is frequently observed in aggressive human cancers.…”
mentioning
confidence: 99%